2010
DOI: 10.1108/17561451011087328
|View full text |Cite
|
Sign up to set email alerts
|

The teaching of law to non‐lawyers

Abstract: PurposeThe paper aims to explore the role of outcome‐based education, criteria‐referenced assessment, and work‐integrated education in the teaching of law to non‐law students. The difficulties inherent in the use of such techniques in this particular context have not yet been thoroughly articulated or theorized because it is not clear what we want of our students: to think like lawyers, to do like lawyers, to be like lawyers – or none of the above. The paper proposes some answers.Design/methodology/approachDis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 26 publications
1
10
0
Order By: Relevance
“…More specifically the study evidence makes a case for Ainul and Siti's (2011) stance, who suggested that the teaching of law modules in professional disciplines, needs to go beyond the surface learning of facts, through to a deeper understanding of issues involved, the links and associated complications. This study, therefore, reinforces the call for a change in teaching delivery styles to non-lawyers as reiterated by earlier studies such as Gerber (2009), Morris (2007Morris ( , 2010 as well as Ainul and Siti (2011), who were of the view that built environment students need specific and subject-relevant modules designed to meet their needs as they enter their chosen professions, with emphasis should be given to the introduction of case studies and scenarios.…”
Section: Delphi Analysis Results and Discussionsupporting
confidence: 81%
See 4 more Smart Citations
“…More specifically the study evidence makes a case for Ainul and Siti's (2011) stance, who suggested that the teaching of law modules in professional disciplines, needs to go beyond the surface learning of facts, through to a deeper understanding of issues involved, the links and associated complications. This study, therefore, reinforces the call for a change in teaching delivery styles to non-lawyers as reiterated by earlier studies such as Gerber (2009), Morris (2007Morris ( , 2010 as well as Ainul and Siti (2011), who were of the view that built environment students need specific and subject-relevant modules designed to meet their needs as they enter their chosen professions, with emphasis should be given to the introduction of case studies and scenarios.…”
Section: Delphi Analysis Results and Discussionsupporting
confidence: 81%
“…The authors asserted that beyond having knowledge of the law relating to ethical issues and the practice of their profession, built environment professionals need to: have knowledge of the relevant sources of law and know how to efficiently locate them; be aware of what possible changes may occur in the relevant areas of law as it pertains to the built environment and the socio-economic impacts such changes may have on their country; Move beyond the superficial learning of law to a more in-depth learning of legal issues; and be able to understand problems within their professional scope, identify legal issues and provide informed reasoning, necessary to handle complications and conflicts. Morris (2010) further emphasizes that a strong understanding of the law is important to built environment professionals because it facilitates intelligent engagement with legal professionals (lawyers) on projects and serves as a preventive and protective mechanism in their practice. Morris (2010, pp.…”
Section: Teaching Law In the Built Environment: Challenges And Issuesmentioning
confidence: 99%
See 3 more Smart Citations